(3GdCbhGd GdbhjeI aj Mce Gdfbd ef GdcJH GdbOjeIs - (3GdHbGYj , EHQGgje Hf YeQ Hf MSf GdQHGW Hf Ydj Hf CHj HcQ GdHbGYj GdTGaYj, HQgGf GdOjf CHh GdMSf,J (B885 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdCaQGO eMShOjf ai cd YUQ Hjf GdYHGO , hPdc Cfi deG UfaJ GdcJGH GdePchQ hgh GdeSei fXe GdOQQ ef JfGSH GdBi hGdShQ s
(3BNQgG (B:s
(3hGNJW HgPG GdcJGH YbGFO GdeSdejf hGafYfG hEjGge Hg jhe dGjfaY eGd hdGHfhf Edi ef CJi Gddg HbdH Sdje hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg CLeYjf Bejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B56 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B71s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B140s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(1539/1) s
Keywords: (3Gdabg GdESdGejs